34‐3: Development of Self‐Alignment Advanced Super Dimensional Switching Technology and Prototype. Issue 1 (29th May 2019) - Yang, Ruizhi; Wu, Jun; Wang, Ruiyong; Wu, Xiaohui; Qu, Lianjie; Xu, Xiaoling; You, Yang; Zhao, Hebin; Feng, Yuanming; Yang, Fucheng; Qi, Xiaojing; Qiu, Yun; et al.
Abstract : There had been little progress in LC alignment method after Photo Alignment (PA) technology especially for homogeneous alignment LCDs. We have developed a prototype in Advanced Super Dimensional Switching (ADS) Mode without using PI layer and rubbing or photo alignment process, but showed almost same level performance as conventional ADS LCDs using PI, which make sense for much more sample process and further possibility to LCDs.